The Influence of Professionalism, Independence, and Auditor Experience on Audit Judgment - RUMIMPUNU, Mohammad Rio; MASRUDDIN, Masruddin; ANSAR, Muhammad; TENRIPADA, Tenripada (Journal of Governance, Taxation and Auditing, 2024)
The study focuses on investigating how audit judgments evolve based on Professionalism combined with Independence and auditor experience within the campaign fund reports compliance audit process targeting the 2024 election participants. The study utilized quantitative investigation and sought responses from auditors at Public Accounting Firms who participated in campaign fund audits by distributing questionnaires based on purposive sampling. Under the multiple regression analysis model through IBM SPSS Statistics, 43 research questionnaires that fulfilled the requirements were evaluated. Testing of hypotheses was performed to measure the influence that Professionalism, together with Independence and auditor experience, have on audit judgment. According to the research data, audit judgment receives positive influence from Professionalism and Independence, yet auditor experience does not impact the judgment significantly. The research reveals that auditor quality depends on professional development together with ethical conduct and maintaining Independence between auditors and their clients. Additionally, the research provides recommendations for auditors and PAFs to prioritize Professionalism and Independence as key factors in producing high-quality audit judgments.